Implementasi Sapta Pesona dalam Perspektif Perbandingan Hukum: Telaah Normatif atas Kebijakan Pariwisata Indonesia dan Standar Hak Asasi Manusia: Implementation of Sapta Pesona in Comparative Law Perspective: Normative Review of Indonesian Tourism Policy and Human Rights Standards - Nowaf Syaefulloh; Muchammad Satrio Wibowo; Wafda Vivid Izziyana; Popova Sonia (Journal of Indonesian Comparative of Syari'ah Law, 2026)
This study aims to analyze the implementation of Sapta Pesona at the Kalipasang Nature Tourism site in Mount Merbabu National Park and its relationship with tourism management policies and human rights principles. The focus of the study is on the extent to which the elements of safety, order, cleanliness, coolness, beauty, friendliness, and memorable experiences are actually applied in the management of conservation-based tourist destinations. The research method used is descriptive qualitative with data collection techniques through field observations, interviews with managers and tourists, documentation, and literature studies. The results show that the implementation of Sapta Pesona at Kalipasang Nature Tourism has been going quite well. The element of safety is realized through routine patrols, the provision of insurance, and warning signs, although the trekking trails still need improvement. Order and cleanliness are supported by a digital ticketing system, parking management, the provision of sanitation facilities, and cooperation with BUMDes. The cool and beautiful environment, friendly service, and positive tourist experience contribute to the sustainability of the destination. Overall, the implementation of Sapta Pesona reflects the synergy between tourism policy and the fulfillment of visitors' basic rights, particularly the right to safety, comfort, and a decent living environment. However, improvements in the quality of facilities and strengthening of safety aspects are still needed so that tourism management can be sustainable and oriented towards respect for human dignity.